ANALISIS SENTIMEN PADA ULASAN PENGGUNA APLIKASI MAXIM MENGGUNAKAN METODE KLASIFIKASI RANDOM FOREST DAN EKSTRAKSI FITUR WORD2VEC - Rafid Ammar Adinegoro (2023)
The industrial revolution 4.0 has caused businesses to start moving into the digital realm, one of which is online transportation. Several online transportation companies have started to appear by launching their business through applications, one of which is Maxim. Along with the increase in the number of application users, the demand for application service quality has also increased. One way to assess an application service is to look at user reviews. This research conducted sentiment analysis on 2 classes, positive and negative, in user reviews of the Maxim application. The classification algorithm used is Random Forest and applies Word2vec feature extraction. Word2vec feature extraction is used to make sentiment analysis more effective because it is able to recognize semantics between words. By testing different Word2vec parameter values, the best performance was obtained at dimension parameters 300, window 7, and epochs 10. The results of this study demonstrate that the Random Forest classification with Word2Vec feature extraction achieved a higher level of performance compared to not using Word2Vec feature extraction, resulting in an accuracy of 93,39%, precision of 95,85%, recall of 91,54%, and an F1-score of 93,65%. In comparison, the performance without using feature extraction only yielded an accuracy of 92,63%, precision of 95,79%, recall of 90,10%, and an F1-score of 92,86%.